Application of Distributed Parallel Computing in Super-Resolution Image Enbancement - Jie Zheng; Sheng Bao; Ying Yang (Dianxin kexue, 2015)
The distributed parallel computing in the super-resolution image enhancement applications was introduced.Super resolution image enhancement refers to improving the image resolution of 1080P video to 4K by software without upgrading existing acquisition device and increasing the transmission bandwidth.Due to the fact that super resolution image enhancement technology needs enormous computing power,super resolution image enhancement system and performance comparison testing by distributed parallel computing was studied.The conclusion shows that the super-image enhancement processing ability can be enhanced hundreds of times with distributed parallel computing technology,so that the production capacity of 4K video can be improved in rea1-world application.